The effects of recycling on the structure and properties of carbon nanotube‐filled polycarbonate. Issue 8 (4th August 2017) - Zhang, Jinde; Panwar, Artee; Bello, Dhimiter; Isaacs, Jacqueline A.; Jozokos, Tim; Mead, Joey
Abstract : Sustainable manufacturing processes are becoming more important in industrial practice. A critical part of the manufacturing process is understanding the recycling behavior of nanocomposite materials, particularly as more recycled plastic nanocomposites are entering the market for a variety of different applications. A common method to recycle thermoplastic composites is by melting and remolding, which often leads to decreased mechanical properties. This work was conducted to investigate the effect of nanofillers on the recycling behavior and structure–property relationships of carbon nanotube (CNT)‐filled polycarbonate (PC). Materials were recycled by repeated injection molding and granulating up to twenty cycles. The effect of recycling on chemical, rheological, and mechanical properties was investigated. The results indicated a general decrease in melt viscosity and mechanical properties (with the exception of Young's Modulus). The CNT‐filled PC shows less resistance to recycling compared to neat PC. POLYM. ENG. SCI., 58:1278–1284, 2018. © 2017 Society of Plastics Engineers